Hepatic CYP Isoforms and Drug-Metabolizing Enzyme Activities in Broiler Chicks - Kawalek, Joseph C.; Myers, Michael J.; Howard, Karyn D.; Farrell, Dorothy E.; Shaikh, Badar (International Journal of Poultry Science, 2006)
Day-old chicks were raised for four - six weeks in pens using different bedding materials (wire, paper, corn cobs, hardwood, rice hulls, cedar, and pine) to determine if these beddings have any effect on hepatic drug metabolizing enzyme activities, cytochrome P450 isoforms, and the disposition of enrofloxacin, a drug previously approved for use in chickens. Cytochrome P450 (CYP) isoforms from the major P450 isoform families (1A, 2A, 2B, 2C, 2D, 2E, 3A, and 4A) and their corresponding hepatic drug metabolizing enzyme activities were measured in subcellular fractions obtained from 4-and 5-week-old birds. Five week-old birds were treated with medicated water containing Baytril at 50 ppm enrofloxacin for five consecutive days and then withdrawn for two days prior to sacrifice. There were no significant differences in P450-mediated reactions or levels of CYP isoforms between any of the different test groups. The marker residue for enrofloxacin was barely detectable in the marker tissue (breast muscle) of the treated birds. The major metabolites of enrofloxacin, namely, ciprofloxacin, desethylenyl-enrofloxacin, and desethylenyl ciprofloxacin, were detectable in extracts of liver homogenates of the treated birds. However, the levels were below the level of quantification.